Study some characteristics of electronic fetal monitoring to diagnose fetal compromise - Nam, Le Phu; Vinh, Truong Quang (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Assessing fetal health during pregnancy and labor is important in reducing neonatal morbidity and mortality. In which electronic fetal monitoring is the most commonly used obstetric procedure. The false-positive rate of electronic fetal monitoring to predict adverse outcomes is high. Therefore, the study of fetal heart rate charts to confirm the diagnosis of fetal compromise is very necessary to limit cases of unreasonable cesarean section. Therefore, we conduct this study to: (1) Survey the characteristics of electronic fetal monitoring (EFM) to diagnose fetal compromise. (2) Find out the association between EFM and obstetrical outcomes Methods: Observative cross-sectional study recruited 336 term singleton pregnant women with occipital presentation, presenting with labour symptoms at Department of Obstetrics and Gynecology, Hue University of Medicine and Pharmacy, between June 2019 to June 2021. All participants accepted to participate in the research and fetal being was assessed by EFM using FIGO 2015 classification. Exclusion criteria were multiple gestation, congenital malformation, placenta previa, placenta abruptio, maternal disease affecting the fetus and using medication which can affect the fetus. Results: Among 336 pregnant women, 31 cases (11%) were diagnosed with fetal compromise. Deceleration had the highest sensitivity while baseline heart rate had the lowest to diagnose fetal compromise. Base line heart rate had the highest specificity while acceleration had the lowest to diagnose fetal compromise. There was an association between EFM and Neonatal Intensive Unit Care admission (p<0.001). There was no association between EFM and gestational age, birth weight, nuchal cord, amniotic fluid’s color and first-minute APGAR score. Conclusions: EFM should be indicated for labour women to screen the fetal compromise. However, abnormal EFM was associated with increased c-section rate, operative delivery and Neonatal Intensive Unit Care admission. Therefore, close monitoring should be combined with clinical and subclinical results to prevent unnecessary intervention